LEADING EDUCATIONAL REFORMS IN CENTRAL ASIA: THE CASE OF KAZAKHSTAN - ZhumaguLov, Bakhytzhan (My University, 2013)
This article is about the leading educational reforms that Kazakhstan should do in the nearest future
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::International education; higher education, Kazakhstan; education reforms; Leadership; country development